Odpowiedzi

2010-01-11T17:49:48+01:00
-11+4x
29+11x
18+5x
50+13x
33+9x
9
15+2x
71+5x
6-5x=3y
2010-01-11T17:50:28+01:00
6+(χ-8)+(3х-9)= 6+x-8+3x-9= -2+4x-9=-11+4x
10(χ+2)-(-3-χ)+6= 10x+20+3+x=11x+23
(9-χ)(2+χ)-χ= 18+9x-2x-x2-x= 18+7x-x2-x=18+6x-x2=-x2+6x+18
-6+(χ-8)+4(3χ-9)=-6+x-8+12x-36=-14+13x-36=13x-50
10(χ+2)-(χ+3)+16=10x+20-x-3+16=9x+17+16=9x+33
(9+χ)(1+χ)-7χ=9+9x+x+x2-7x=2+10x+x2-7x=x2+3x+2
6+(χ+18)+(χ-9)=6+x+18+x-9=24+2x-9=2x+15
4(χ-2)-(3-χ)-60=4x-8-3+x-60=5x-11-60=5x-71
(3-χ)(2+χ)-5χ=3γ= tu chyba miało być na koncu +3y więc tak licze!
(3-χ)(2+χ)-5χ+3y= 6+3x-2x-x2-5x+3y=6+x-x2-5x+3y=-x2-4x+3y+6